Height with the ability to lay up basketball games: Is there a relationship? - Hardinata, Riyan; Ahwan, M. Tami Rosadi; Damastuti, Eviani; Nugroho, Wiyan Fauzi; Urahman, Taufik; Abidin, Muhammad Zainal; Hamsa, Hamsa; Mustotiah, Mustotiah (Tanjungpura Journal of Coaching Research, 2023)
This study aims to see whether height and lay up ability in basketball games have a relationship. This research is descriptive quantitative with a correlation study. The research was conducted in November 2022 with the population at SMA Negeri 3 Banjarbaru. The sample used was class XI IPA 3 and the sampling technique used random sampling so that a sample of 36 students was obtained. The instruments in this study were height using a microtoise, and lay up with a basketball, basketball court complete with a ring. Data analysis using SPSS application. The results showed a significance value of 0.008 <0.05, so there is a significant relationship. Conclusion height and lay up ability have a significant relationship.